2016
DOI: 10.3233/ch-152019
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic nerves: How do they affect angiogenesis, particularly during wound healing of soft tissues?

Abstract: Angiogenesis is essential for wound healing, and angiogenesis impairment can result in chronic ulcers. Studies have shown that the sympathetic nervous system has an important role in angiogenesis. In recent years, researchers have focused on the roles of sympathetic nerves in tumor angiogenesis. In fact, sympathetic nerves can affect angiogenesis in the wound healing of soft tissues, and may have a similar mechanism of action as that seen in tumorigenesis. Sympathetic nerves act primarily through interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…The enhanced expression of angiogenic factors in ECM/SVF-gel and a rich vascular network around the wound area indicated that the faster healing of wounds in the ECM/SVF-gel group could be attributed to increased vascularization. Vascularization of the wound bed is known to play a significant role in the wound healing process [ 13 , 14 ]. Recent cytotherapy strategies using MSCs have aimed at increasing vascularization to achieve wound healing due to their paracrine effects and differentiating potential [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced expression of angiogenic factors in ECM/SVF-gel and a rich vascular network around the wound area indicated that the faster healing of wounds in the ECM/SVF-gel group could be attributed to increased vascularization. Vascularization of the wound bed is known to play a significant role in the wound healing process [ 13 , 14 ]. Recent cytotherapy strategies using MSCs have aimed at increasing vascularization to achieve wound healing due to their paracrine effects and differentiating potential [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between these three features in the diabetic foot is not completely clear. Sympathetic nerve activity may correlate with reepithelialization, neurogenic inflammation [12], collagen metabolism, and angiogenesis [6]. The role of sympathetic nerve failure in DFUs remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The role of sympathetic nerve failure in DFUs remains controversial. Sympathetic nerves are located near pericytes in the microvessels [6]. It has not been reported how sympathetic denervation affects inflammation and angiogenesis in DFUs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations